Markasan Strategy in A Best-Selling Music (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
Gesang and Didi Kempot, in dominating the market of the music industry in their era, incorporated local capital, i.e., the site in lyrics and scales in melody. Likewise with Markasan. However, little is known about the site and melody used by Markasan as a tool to dominate the keroncong market in East Java in the 1960-1965 period. This study aims to reveal lyrics and melody that songwriters can use to dominate the music competition market in their day. To address this gap, observations, interviews, and documentation studies were carried out. The subjects are Keroncong-Markasanan musicians and RRI as melting pots of keroncong in Surabaya. Through ‘Blauran Wayah Sore’ song, we can observe Markasan’s efforts to construct songs, build resistance, and perpetuate domination in the music industry competition in his day. This research provides a strategy to utilize cultural capital consisting of lyric styles, popular site names, local scales, and identification of favorite song scales in a best-selling effort in the music industry today.